Етюди Миколи Кравчука - Ткаченко, Т. (Філологічний дискурс, 2019)
Статтю присвячено дослідженню творчого доробку Миколи Кравчука (1929–2009). Увагу зосереджено на етюді як літературному жанрі, умовній класифікації художньої спадщини прозаїка, зважаючи на центральну постать у творі. Висвітлено формальні та змістові складники, локальну визначеність, унікальну текстову організацію, роль зображально-виражальних засобів, значення рефрену й епіграфів, особливості характеротворення. З’ясовано специфіку автобіографічної нарації та саморефлексії, риси ідіостилю письменника. The article devotes to the study of the work of Mykola Kravchuk (1929–2009). It focuses on the etude as a literary genre, the conditional classification of the writer’s artistic heritage, despite the central figure in the work. This paper highlightes the formal and substantive components, in particular, the topics and issues, local certainty, unique textual organization, the role of graphic expressive means, the value of refrain and epigraphs, the portraits of characters (speech, detail). The investigation reveals the specificity of the autobiographical and self-reflection, worldview and features of the writer’s idiostyle.